Innovation Factors and its Effect on the GDP Per Capita of Selected ASEAN Countries: An Application of Paul Romer's Endogenous Growth Theory - Apostol, Matthew; Enriquez, Hans Angelo; Sumaway, Odette; Navarrete, Al Faithrich (International Journal of Social and Management Studies, 2022)
Romer’s endogenous growth theory highlighted the importance of intentional actions and efforts made by firms to cultivate a culture of innovation and ideas and its eventual effects on economic growth. This study aims to measure whether there is a positive relationship between innovation using Urbanization (URB), research and development (R&D), and human capital (HC) oneconomic growth. Innovation will be represented by the URB rate per percentage in total population, research and development (R&D), and HC will be assessed using its GlobalInnovation Index ratings. Economic growth will be measured using the Log of Gross Domestic Product (LGDP) per capita. This study will utilize a panel data regression, Pooled Ordinary LeastSquare analysis, to determine the relationship in the selected Association of Southeast Asian Nations countries (Indonesia, Malaysia, Philippines, Vietnam) between the years 2013-2020. Results show that URB and HC significantly impact LGDP per capita, while R&D is insignificant. The insignificance found in this study can be explained by the fact that the countries selected aredeveloping countries and that it would take time for R&D to impact their economic growth. Despite the insignificant impact of R&D activities, they should still be actively promoted in these countries, as it will gradually increase the level of innovation with time as explained in the long-run increasing returns of scale and the endogenous growth theory, thus proves Romer’s theory is present in Indonesia, Malaysia, Philippines, Vietnam.